PENGARUH PENGELUARAN PEMERINTAH, PENGANGGURAN DAN PERTUMBUHAN EKONOMI TERHADAP TINGKAT KEMISKINAN DI PROVINSI KALIMANTAN SELATAN - HENNY KHAMILAH (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
This study entitled "The Effect of Government Expenditure, Unemployment and Economic Growth on Poverty Rate in South Kalimantan Province".               The purpose of this research is to know the effect of Government Expenditure, Unemployment Rate and Economic Growth on Poverty Level in South Kalimantan Province.               The method of analysis used is multiple linear regression time series data of this research using observation of 11 years from 2006 until 2016 existing data processed by using tool of computer program E-views 9.0.               Based on the result of the research, the result of government expenditure has positive and insignificant influence to poverty rate in South Kalimantan Province, unemployment has positive and significant effect to poverty level in South Kalimantan Province, economic growth has negative and insignificant effect on poverty level in South Kalimantan Province.Keywords: Government Expenditure, Unemployment, Economic Growth andPoverty Level